WEDDING RSVP ONLINE SYSTEM - Elizabeth, Ubam (Universiti Malaysia Sarawak (UNIMAS), 2020)
This project is a web-based system that acts as website whereby the guests can RSVP through online. This system will also help the wedding planner or the bride and groom to be able to keep track of the RSVPs, manage checklists and manage details of the wedding. With this online system, it will allow them to manage the guest list attendance more efficiently. This will help them to overcome the problem of managing the guest lists attendance manually especially when dealing with a huge number of invitations. As for the guests whom are the users of the system, this proposed system is convenient for them because they will be able to respond with only a few clicks away.